Distractibility, anxiety, irritability, and agitation symptoms are associated with the severity of depressive and manic symptoms in mixed depression - Tavares,Diego Freitas (2022)
Objective: To explore whether there is an association between distractibility, anxiety, irritability, and agitation (DAIA) symptoms and the severity of depressive and manic symptoms. Methods: Patients with unipolar and bipolar disorder (I and II) and mixed depression were evaluated. DAIA symptoms were assessed using previously described definitions. Results: The full analysis set comprised 100 patients. The severity of depressive symptoms in mixed depression, assessed by Montgomery-Åsberg Depression Rating Scale (MADRS), was significantly associated with the presence of two or more DAIA symptoms in the bipolar sample, influenced mainly by anxiety. The severity of manic symptoms in mixed depression, assessed by Young Mania Rating Scale (YMRS), was significantly associated with the presence of two or more DAIA symptoms in the bipolar sample and three or four DAIA symptoms in the unipolar sample. Conclusion: DAIA symptoms were associated with greater severity of manic symptoms in mixed depression. DAIA symptoms must be evaluated in all patients with mixed features and are associated with the severity of depressive and manic symptoms in mixed depression. Clinical trial registration: ClinicalTrials.gov (NCT04123301).